Management Of Strengthening Character Education In Fostering Morals Of Karimah Students At Madrasah Tsanawiyah, Bandung Regency - Arifin, Furqon; Ulfiah, Ulfiah; Sauri, Supyan; Koswara, Nandang (CV. Inara, 2022)
This research is motivated by the thought of developing character education, especially in the world of education as a strategic step for the sustainability and excellence of the nation in the future. The world of education is a world that is expected to shape the character of the young generation of the Indonesian nation, considering that character education is the main priority in the educational goals of the current government. In accordance with the reference to President Joko Widodo's vision, namely carrying out a